HUBUNGAN ANTARA PENGETAHUAN NUTRISI DENGAN OBESITAS PADA MAHASISWA PENDIDIKAN DOKTER FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA - Janice, Elisabeth; Tirtayasa, Ketut; Juhanna, Indira Vidiari; Wahyuni, Nila (E-Jurnal Medika Udayana; Vol 12 No 3 (2023): E-Jurnal Medika UdayanaDO - 10.24843/MU.2023.V12.i03.P18, 2023)
Background. Obesity is one of problems that are often found in students due to the lifestyle of students who are less active. Changes in student lifestyles to become sedentary have an impact on eating patterns, or the consumption of people who are more likely to choose fast food, high-calorie, and high-fat foods. Nutrition knowledge is known to affect a person's diet. Diet itself certainly affects the type of food and the amount of food consumed every day. People with high nutrition knowledge will be able to regulate their daily diet and avoid one of the risks of obesity. Purpose. To know the relationship between nutritional knowledge and obesity. Method. Type of research used is an analytical cross sectional research method to analyze the relationship between nutrition knowledge and BMI among medical students in Udayana University. Results. The samples that were collected were 98 people, the results obtained in this study showed that 53.1% of students had a normal BMI and 48% of students had low nutritional knowledge. Based on this study, it was found that the p value was 0.588 and it can be concluded that there is no relationship between nutritional knowledge and obesity